Імператив національної ідентичності у прозі Галини Журби - Мафтин, Н. (Слово і Час, 2008)
Авторка розкриває особливості художнього світобачення Галини Журби,
властиві її прозі 1930-х років. Досліджується також вплив
націєутверджувальної риторики на художньо-поетикальні засоби та
специфіку композиції повістей письменниці. This article singles out the essential features of Halyna Zhurba’s artistic worldview, which served as a
foundation of her prose of the 1930s and determined the originality of her texts within the literary discourse
in Halychyna. The author of the article also studies the influence of nation"consolidating rhetoric on the
writer’s stylistic and poetic devices as well as on the specific composition of her prose. Автор раскрывает характерные черты
художественного мировоззрения малоизвестной и
на сегодня украинской писательницы, которые
стали определяющими в ее творчестве 30-х годов и обозначили оригинальность ее нарратива. Исследуется также влияние нациоутверждающей на художественные приемы и специфику композиции повестей писательницы.